P50 Suppression and Its Neural Generators in Antipsychotic-Naïve First-Episode Schizophrenia Before and After 6 Months of Quetiapine Treatment - Oranje, Bob (Oxford University Press, 2013)
Background: Numerous studies have demonstrated sensory gating deficits in schizophrenia. However, only a few longitudinal studies report on the effects of antipsychotic treatment on sensory gating deficits and their results are inconsistent. In the present study, P50 suppression and its neural generators were investigated in antipsychotic-naïve first-episode patients with schizophrenia before and after 6 months of treatment with quetiapine. Methods: Thirty-four antipsychotic-naïve first-episode schizophrenia patients and age and gender matched healthy controls were tested in an auditory sensory gating paradigm at baseline and after 6 months. During this period, the patients were treated with quetiapine, while controls received no treatment. Sixteen patients completed the study. Results: Patients showed significant reduced P50 suppression compared with controls at baseline but not at follow-up. Furthermore, a significant positive correlation between baseline P50 suppression and dose of quetiapine at follow-up was found. P50 suppression in patients receiving above median dosages of quetiapine increased significantly from baseline to follow-up. At baseline, a frontocentral source was significantly more active in patients than in controls at the time of the testing stimulus. Conclusions: The present findings suggest that P50 suppression deficits are already present at an early stage of schizophrenia. Furthermore, particularly those patients with more severe gating deficits appeared to need higher dosages of quetiapine, although their clinical symptoms did not seem to indicate this. Quetiapine treatment significantly improved these gating deficits. Furthermore, a frontocentral source in the brain appeared to be involved in the deficient P50 gating of the patients.